Etnomusiklopedia: A Comprehensive Digitization Model for Preserving Indonesia’s Musical Heritage - Aryandari, Citra; Nurvijayanto, Ribeth; Manurung, Sopandu (Khazanah: Jurnal Pengembangan Kearsipan, 2026)
Indonesia's ethnomusicological heritage, documented since Jaap Kunst's early 20th-century works, remains largely inaccessible due to fragmented archival systems and analog-based documentation. This research addresses the "archival accumulation crisis" by developing a system called Etnomusiklopedia, a comprehensive digitization model that integrates four core dimensions of ethnomusicology—organology, performance practice, cultural context, and sonic documentation—within a unified digital ecosystem. Employing Design Science Research (DSR) methodology, we designed a relational database architecture featuring context-rich metadata, semantic search capabilities, and community-centered curation mechanisms. Validation with ethnomusicology practitioners and cultural stakeholders demonstrates significant improvements in accessibility of knowledge and efficiency of cross-referencing compared to conventional archival systems. Beyond technological innovation, this model addresses critical ethical dimensions of digital heritage management, emphasizing meaningful community participation to prevent recolonization of indigenous knowledge. The research contributes both a functional prototype and a theoretical framework for cultural heritage digitization that transform archives from passive repositories into active tools for community empowerment and knowledge reclamation.